A conceptual framework for ranking the multiple intelligences of people with epilepsy - Rezaie, V. (IEEE, 2012)
Intelligence of a person can be enhanced if the person focuses and practices regularly. ATIE©, a psychometric test, was developed based on the Multiple Intelligence (MI) theory of Howard Gardner to measure eight types of intelligence skills namely musical, kinesthetic, math-logic, spatial, verbal, interpersonal, intrapersonal and naturalist. The inverse model of ATIE , Fuzzy Inverse ATIE (FIA) was developed to get the best intelligence parameters that would be garnered to maximize the employment probability of people with epilepsy (PWE). In this paper, we present a conceptual framework of a model to rank the suggested intelligences obtained from FIA which are to be improved. This information is essential in order to improve the chances of PWE to be employed.